Fatigue crack growth in the 2050-T8 aluminium alloy. (October 2018) - Antunes, F.V.; Serrano, S.; Branco, R.; Prates, P.
Abstract: Fatigue crack growth (FCG) is usually studied using ΔK, however several limitations have been found in the use of da/dN-ΔK curves. Therefore, the FCG in the 2050-T8 aluminium alloy is studied here using the plastic CTOD. Experimental work was developed to obtain FCG in M(T) specimens. The experimental procedure was replicated numerically in terms of geometry, loading and material behaviour. The cyclic plastic behaviour of the material was modeled using stress-strain curves obtained in low-cycle fatigue tests. Numerical predictions of plastic CTOD were obtained for different crack lengths and a da/dN versus plastic CTOD model was built. This model was used to predict the effect of variable amplitude loading, namely, overloads and load blocks. All the predictions agreed qualitatively with the known effect of the load patterns studied. Crack closure was found to be a main mechanism behind the variations of plastic CTOD and therefore of da/dN.